Право на оскарження судових рішень у кримінальних справах у світлі норм Конвенції про захист прав людини та основоположних свобод1950 р. - Фідря, Ю.; Fidria, Ju. (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті висвітлено окремі питання регламентації у законодавстві України права на оскарження судових рішень у кримінальних справах, гарантованого Конвенцією про захист прав людини та основоположних свобод1950 року, а також проаналізовано прецедентну практику Європейського суду з прав людини у цій сфері. Механізм реалізації права на оскарження досліджено крізь призму інстанційності – принципу побудови національної системи судів загальної юрисдикції. Проаналізовано колізійний вплив принципів правової визначеності таres judicata, з одного боку, та права на ефективний судовий захист, з іншого, на формування системи оскарження та перегляду рішень судів в Україні. Основним завданням законодавця у даному випадку є досягнення оптимального балансу публічно-правових та приватно-правових інтересів шляхом чіткого встановлення підстав, умов та порядку перегляду судових рішень. The article considers some issues regulating the right to appeal against court decisions on criminal matters in the legislation Ukraine, which is guaranteed by the Convention on Human Rights and Fundamental Freedoms 1950. The author analyzes the case law practice of the European Court on Human Rights. The mechanism of investigation of the right to appeal has been examined in the light of ‘instances’ principle- the model of national system of courts of general jurisdiction, and in the context of controlling the stages of thecriminal process system. The author emphasizes that the Conflict of laws principles and res judicata, on the one hand,and the right to an effective court protection, on the other hand, have a great impact on the formation of the appeal system and review of court decisions in Ukraine. The main task of the legislator in this case is to achieve the optimum balance of public-private and private-legal interests by establishing accurate bases, conditions and order of judicial decisions revision. The practice of national courts and the European Court on Human Rights in recent years has revealed a number of problems that impede the effective implementation of the right to appeal. These problems largely concern the stages of adopting judicial decisions in revision of criminal cases and, according to the author, are tobe considered both in the theoretical and practical aspects.
Right to Appeal Against Court Decisions on Criminal Matters in the Light of the Norms of the Convention on Human Rights and Fundamental Freedoms 1950.
Keywords: європейські стандарти кримінального судочинства; апеляційне провадження; касаційне провадження; інстанційність; стабільність судового рішення; European standards of criminal justice; appeal; cassation proceedings; instances; stability of court decision